Review of Posthümanizm: Kavram, Kuram, Bilim-Kurgu - Arıkan, Seda (İngiliz Dili ve Edebiyatı Araştırmaları Derneği / English Language and Literature Research Association of Turkey, 2023)
Reviewed Book: Posthümanizm: Kavram, Kuram, Bilim-Kurgu, by Başak Ağın, Ankara, Siyasal Kitabevi, 2020, pp. 244, ?58,50 (paperback), ISBN: 9786057877703.

Reviewed Book: Posthümanizm: Kavram, Kuram, Bilim-Kurgu, by Başak Ağın, Ankara, Siyasal Kitabevi, 2020, pp. 244, ?58,50 (paperback), ISBN: 9786057877703.
Review of Posthümanizm: Kavram, Kuram, Bilim-Kurgu
Keywords: Literary Theory; Edebi Teori